PERFORMANCE CHARACTERISTICS OF AN ARMATURE VOLTAGE CONTROLLED D.C. MOTOR (Nigerian Journal of Technology, 2003)
In this paper, the performance study of a separately excited d. c. motor whose speed is controlled by armature voltage variation is presented. Both the open loop and the closed loop steady state and transient characteristics are reported. The speed controllers considered in the closed loop mode are the proportional and the proportional plus integral types. To each of these two control arrangements is added an inner current controller loop. Using developed motor equations, the performance characteristics of a test motor are obtained by digital computer analysis. The results show that closed loop operation, with appropriate control gains, give improved speed regulation and response characteristics for the d. c. drive system.